2009
DOI: 10.4049/jimmunol.0902404
|View full text |Cite
|
Sign up to set email alerts
|

The Kinase Inhibitors Sunitinib and Sorafenib Differentially Affect NK Cell Antitumor Reactivity In Vitro

Abstract: Sunitinib and Sorafenib are protein kinase inhibitors (PKI) approved for treatment of patients with advanced renal cell cancer (RCC). However, long-term remissions of advanced RCC have only been observed after IL-2 treatment, which underlines the importance of antitumor immune responses in RCC patients. Because PKI, besides affecting tumor cells, also may inhibit signaling in immune effector cells, we determined how Sunitinib and Sorafenib influence antitumor immunity. We found that cytotoxicity and cytokine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
70
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 43 publications
8
70
0
1
Order By: Relevance
“…The present study has confirmed in vivo what was previously demonstrated by Krusch et al (16) in vitro; specifically, there is no negative influence to NK cells CD107a expression and no decline in cytokine production, including of IFN-γ, by PBMC when treated with sunitinib. The enhanced activity rate of PBMC and NK cells during and prior to therapy with sunitinib may be associated with the underlying disease mechanics of mRCC.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study has confirmed in vivo what was previously demonstrated by Krusch et al (16) in vitro; specifically, there is no negative influence to NK cells CD107a expression and no decline in cytokine production, including of IFN-γ, by PBMC when treated with sunitinib. The enhanced activity rate of PBMC and NK cells during and prior to therapy with sunitinib may be associated with the underlying disease mechanics of mRCC.…”
Section: Discussionsupporting
confidence: 92%
“…Within the last two decades, numerous new strategies have been developed to improve overall survival, quality of life and disease regression in patients with advanced RCC (1,(4)(5)(6)16,19), and TKI therapy has been shown to be an important treatment modality in addressing these objectives (10,12,13). Nevertheless, data are limited on how TKIs may interact with the immune system of an individual patient (16,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sorafenib reportedly inhibits cytotoxicity and IFNg production of both resting and activated human NK cells (39). In mice, sorafenib reduced the number of NK cells and their activity against tumor cells (40).…”
Section: Discussionmentioning
confidence: 99%